Formulation of a novel antibacterial topical treatment based on Magnetite-Buforin-II-silver nanobioconjugates - Muñoz, Laura N.; Jaramillo, Valentina; Gantiva-Diaz, Mónica; Cifuentes, Javier; Muñoz-Camargo, Carolina; Cruz, Juan C.; González Barrios, Andrés Fernando (Frontiers in Bioengineering and Biotechnology, 2022)
Community acquired infections caused by Meticillin-resistant Staphylococcus aureus (MRSA) have become a growing concern due to its impact on the world public health. This microorganism is a commonly spreading pathogen associated predominantly with skin infections and connected to other more severe conditions (septic shock, and generalized infection). The lack of highly effective antibiotics and treatments to control skin infections with S. aureus has led to the search of novel therapies using alternative agents such as antimicrobial peptides (AMPs). In order to obtain a viable administration route to counteract superficial skin infections (impetigo, abscesses, furuncles, and cellulitis), a topical formulation based on Magnetite-Buforin-II-silver nanobioconjugates as active antibacterial agents was designed by their dispersion in O/W concentrated emulsions. The prepared topical characterization indicated that O/W emulsions were stable in time, the droplets size remained within the appropriate values (∼1 µm) and their rheological properties, such as pseudoplastic and shear-thinning behavior, remained unchanged for up to 3 months. Additionally, hemolysis and platelet aggregation tests were acceptable (i.e., 14.72 ± 2.62% and 8.06 ± 2.90%, respectively) in compliance with the ISO-10993 standard. Furthermore, the treatment reduced significantly (p < 0.0001) the growth of both clinical isolated MRSA and wild Type S. aureus strains as evidenced by the contact diffusion method. These results are important in the context of proposing new alternatives that allow manage effectively the threat posed by the antibiotic resistant bacterial strains, which jeopardize the lives of thousands of people every year.